Quantitative Study Of Antibiotic Use In Patients With Urinary Tract Infections At Rsu X In East Jakarta 2019 - Delina Hasan; Yardi Yardi; Rosa Amalia (Ridwan Institute, 2023)
Urinary tract infection is a health problem that can increase morbidity and even increase the death rate both in Indonesia and in the world. Urinary tract infection is the second most common infectious disease after upper respiratory tract infection which in its treatment must use antibiotic therapy, so the treatment must be appropriate and rational. The purpose of this study was to determine the use of antibiotics quantitatively using the ATC/DDD and 90% DU methods in patients with urinary tract infections at RSU X in East Jakarta. Methods, This research is a descriptive study using a crosssectional design. Data collection was carried out retrospectively through the medical records of urinary tract infection patients at RSU the inclusion and exclusion criteria. The results showed that the total DDD/100 patientdays in this study was 96.65% with the highest type of antibiotic, namely levofloxacin, 44.07% DDD/100 patientdays. Drugs included in the DU segment 90% were levofloxacin (45.60%), ceftriaxone (21.54%), cefoperazone (11.33%), and amoxicillin clavulanate (9.00%). Keywords: Antibiotics, urinary tract infection, ATC/DDD, 90% DU.